Denosumab versus zoledronic acid in bone disease treatment of newly diagnosed multiple myeloma: an international, double-blind, double-dummy, randomised, controlled, phase 3 study - Raje, Noopur; Terpos, Evangelos; Willenbacher, Wolfgang; Shimizu, Kazuyuki; García-Sanz, Ramón; Durie, Brian; Legieć, Wojciech; Krejčí, Marta; Laribi, Kamel; Zhu, Li; Cheng, Paul; Warner, Douglas; et al. (The Lancet. Oncology, 2018)
BACKGROUND: Multiple myeloma is characterised by monoclonal paraprotein production and osteolytic lesions, commonly leading to skeletal-related events (spinal cord compression, pathological fracture, or surgery or radiotherapy to affected bone). Denosumab, a monoclonal antibody targeting RANKL, reduces skeletal-related events associated with bone lesions or metastases in patients with advanced solid tumours. This study aimed to assess the efficacy and safety of denosumab compared with zoledronic acid for the prevention of skeletal-related events in patients with newly diagnosed multiple myeloma. METHODS: In this international, double-blind, double-dummy, randomised, active-controlled, phase 3 study, patients in 259 centres and 29 countries aged 18 years or older with symptomatic newly diagnosed multiple myeloma who had at least one documented lytic bone lesion were randomly assigned (1:1; centrally, by interactive voice response system using a fixed stratified permuted block randomisation list with a block size of four) to subcutaneous denosumab 120 mg plus intravenous placebo every 4 weeks or intravenous zoledronic acid 4 mg plus subcutaneous placebo every 4 weeks (both groups also received investigators' choice of first-line antimyeloma therapy). Stratification was by intent to undergo autologous transplantation, antimyeloma therapy, International Staging System stage, previous skeletal-related events, and region. The clinical study team and patients were masked to treatment assignments. The primary endpoint was non-inferiority of denosumab to zoledronic acid with respect to time to first skeletal-related event in the full analysis set (all randomly assigned patients). All safety endpoints were analysed in the safety analysis set, which includes all randomly assigned patients who received at least one dose of active study drug. This study is registered with ClinicalTrials.gov, number NCT01345019. FINDINGS: From May 17, 2012, to March 29, 2016, we enrolled 1718 patients and randomly assigned 859 to each treatment group. The study met the primary endpoint; denosumab was non-inferior to zoledronic acid for time to first skeletal-related event (hazard ratio 0·98, 95% CI 0·85-1·14; pnon-inferiority=0·010). 1702 patients received at least one dose of the investigational drug and were included in the safety analysis (850 patients receiving denosumab and 852 receiving zoledronic acid). The most common grade 3 or worse treatment-emergent adverse events for denosumab and zoledronic acid were neutropenia (126 [15%] vs 125 [15%]), thrombocytopenia (120 [14%] vs 103 [12%]), anaemia (100 [12%] vs 85 [10%]), febrile neutropenia (96 [11%] vs 87 [10%]), and pneumonia (65 [8%] vs 70 [8%]). Renal toxicity was reported in 85 (10%) patients in the denosumab group versus 146 (17%) in the zoledronic acid group; hypocalcaemia adverse events were reported in 144 (17%) versus 106 (12%). Incidence of osteonecrosis of the jaw was not significantly different between the denosumab and zoledronic acid groups (35 [4%] vs 24 [3%]; p=0·147). The most common serious adverse event for both treatment groups was pneumonia (71 [8%] vs 69 [8%]). One patient in the zoledronic acid group died of cardiac arrest that was deemed treatment-related. INTERPRETATION: In patients with newly diagnosed multiple myeloma, denosumab was non-inferior to zoledronic acid for time to skeletal-related events. The results from this study suggest denosumab could be an additional option for the standard of care for patients with multiple myeloma with bone disease. FUNDING: Amgen.
Keywords: výsledek terapie; nádory kostí; komprese míchy; Male; protinádorové látky; Bone Neoplasms; doba přežití bez progrese choroby; Risk Factors; Fractures, Spontaneous; fraktury spontánní; Aged; Multiple Myeloma; mužské pohlaví; senioři; dvojitá slepá metoda; Treatment Outcome; Time Factors; Bone Density Conservation Agents; lidé; ženské pohlaví; Humans; denosumab; Zoledronic Acid; Spinal Cord Compression; časové faktory; rizikové faktory; kyselina zoledronová; inhibitory kostní resorpce; Double-Blind Method; mnohočetný myelom; Female; Progression-Free Survival; lidé středního věku; Denosumab; Antineoplastic Agents; Middle Aged